An intermediate layer catalyst in bipolar membranes: Ti3CNTx MXene - Celik, Aytekin; Aksoy, Yunus; Yegin, Mustafa; Hanay, Ozge; Hasar, Halil (Springer, 2025)
Bipolar membranes (BPMs) play a vital role in electrochemical applications, where robust interfacial design is essential for efficient ion separation. This study investigates the effects of Ti3CNTx MXene, synthesized from the Ti3AlCN MAX phase via HF and LiF + HCl etching routes, as a catalytic component in the intermediate layer of BPMs. To fabricate functional BPMs, polysulfone (PSU) was modified with sulfone and amine groups through sulfonization and amination, forming the necessary cationic and anionic exchange layers. XRD confirmed the complete removal of aluminum, while FTIR and H-1-NMR analyses verified successful polymer functionalization. Comprehensive characterization of the MXene-based BPMs included contact angle measurements, electrical resistance, water uptake capacity, and dynamic mechanical analysis (DMA). Notably, mechanical properties improved with MXene addition-Young's modulus increased from 635 MPa (BPM-1/PS) to 1135 MPa (BPM-3/PS). Water uptake values ranged from approximately 10% in BPM-1/PS to approximately 23% in BPM-6/PS, and electrical resistance measurements showed that BPM-1/PS had the lowest resistance (similar to 0.26 Omega.cm(2)), while BPM-2/PS recorded the highest (similar to 2 Omega.cm(2)). These findings highlight the significant impact of MXene on both mechanical integrity and hydrophilicity, indicating a trade-off between these properties depending on loading and dispersion. The study demonstrates the potential of MXene-enhanced BPMs for high-performance use in electrodialysis, fuel cells, and wastewater treatment systems.
Keywords: MXene; Ti3CNTX; Intermediate layer; Bipolar membrane